The External Electric Field Effect to Hydrogen Storage on B-N Co-Doped Graphene Surface Decorated by Metal Atoms: A DFT Study - A. Sarmada; Susiani Pupon (JPSE (Journal of Physical Science and Engineering), 2019)
Hydrogen has been concerned to be an ideal clean energy carrier among the other renewable energy sources because of its environmental friendliness. However, some challenges have to be addressed before hydrogen will become a conventional and commonly available energy carrier. For instance, the volumetric energy of hydrogen has an issue such as controlling in ambient condition with reliable utilities in nowadays gadget that from day-to-day become lighter and lighter. Recently, carbon-based materials such as graphene and carbon nanotubes have been designed for hydrogen storage due to their large surface area, lightweight, and tunable properties. In this study, we have considered Boron and Nitrogen co-doped graphene surface (BNDG) because B–N pair is isoelectronic to the C–C pair and investigated its hydrogen storage capacity by decorating  different metal atoms. However, controlling the binding strength of metal atoms with that of the BNDG surface is an important issue in the application of hydrogen storage. The recent studies have shown that the binding strength between the metal atom and the substrate can be controlled by means of applying an external electric field. Thus, the effects of the external electric field on the designed medium towards its hydrogen storage capacity is explored. Using density functional theory approach, we showed the adsorption energy of molecular hydrogen as the key of storage capacity on the B, N doped graphene increased due to the higher applied electric fieldHydrogen has been concerned to be an ideal clean energy carrier among the other renewable energy sources because of its environmental friendliness. However, some challenges have to be addressed before hydrogen will become a conventional and commonly available energy carrier. For instance, the volumetric energy of hydrogen has an issue such as controlling in ambient conditions with reliable utilities nowadays gadgets that from day-to-day become lighter and lighter. Recently, carbon-based materials such as graphene and carbon nanotubes have been designed for hydrogen storage due to their large surface area, lightweight, and tunable properties. Controlling the binding strength of metal atoms with that of the BNDG surface is an important issue in the application of hydrogen storage. Recent studies have shown that the binding strength between the metal atom and the substrate can be controlled by means of applying an external electric field. In this study, we have considered Boron and Nitrogen co-doped graphene surface (BNDG) because B–N pair is isoelectronic to the C–C pair and investigated its hydrogen storage capacity by decorating different metal atoms. We utilize the DFT calculations study to investigate the hydrogen storage properties materials. By applying an external electric field on the Ti3 decorated BNDG sheet, we have demonstrated that the adsorption energy of H2 molecules can be increased substantially and thereby can tune the overall hydrogen storage capacity. These theoretical predictions can serve as a guiding reference to experimental works in developing efficient hydrogen storage materials for practical implementations. DOI: http://dx.doi.org/10.17977/um024v4i22019p074